On introduction of Black Sea mussel Mytilus galloprovincialis (Lamarck, 1819) to the Caspian Sea basin - E. V. Minakova; O. V. Zhatkina; R. D. Kashin; A. V. Mikhailova; N. V. Kozlova; E. Yu. Tikhonova (Известия ТИНРО)
Large-sized specimens of a new for the Caspian Sea mollusk were found in spring 2023 in trawl catches of the survey conducted by the Volga-Caspian branch (CaspNIRKH) of the Russian Res. Inst. of Fisheries and Oceanography. Using molecular genetics research methods, including sequencing of the cytochrome oxidase gene of mitochondrial DNA, the species is identified as Mytilus galloprovincialis — the Black Sea mussel. In summer, the invaders were recorded in bottom samples in several areas of the sea. Features of the species biology allow its naturalization into the Caspian Sea ecosystem that will contribute to enrichment of the food base for fish and involve this filter-feeding mollusk to the processes of self-purification of the sea.